Advanced Cathode Materials for Sodium‐Ion Batteries: What Determines Our Choices?. Issue 5 (25th April 2017) - Dai, Zhengfei; Mani, Ulaganathan; Tan, Hui Teng; Yan, Qingyu
Abstract : Among the various energy solutions, lithium‐ion batteries (LIBs) play an important role in the process of the transition from fossil fuels to renewables. However, the necessity to replace lithium with cheaper alternatives due to its scarcity has recently attracted great interest to developing sodium‐ion batteries (SIBs). Hence, the discovery and development of suitable cathode materials that exhibit high specific capacity, good cycling stability, and high energy density are actively pursued. Today's SIB technology continues to be driven by the performance of the cathode materials. Here, recent advancements made regarding the cathode of SIBs are summarized, covering some of the fundamental aspects of SIBs, synthetic protocols, and characteristics of existing and prospective cathode materials used for SIBs. Furthermore, some of the latest achievements in the fabrication of cathode materials, as a practical demonstration on their viability, are also discussed. With better understanding of these topics, the rationales behind their enhanced electrochemical performances are revealed and explained. Last but not least, imminent challenges and future prospects are also included to provide some insights into the possible development of advanced cathode materials for SIBs. Abstract : Recent advances made regarding the cathode of sodium‐ion batteries (SIBs) are summarized, covering the fundamental aspects, synthesis protocols, and characteristics of existing cathode materials. Some of the latest achievements in SIB cathode materials, as a practical demonstration of their viability, are also discussed. Imminent challenges and future prospects are included to provide some insights into possible choices of advanced cathode materials for SIBs.